Epicutaneous administration of the pattern recognition receptor agonist polyinosinic‐polycytidylic acid activates the MDA5/MAVS pathway in Langerhans cells. Issue 8 (6th March 2018) - Tajpara, Pooja; Schuster, Christopher; Schön, Elisabeth; Kienzl, Philip; Vierhapper, Martin; Mildner, Michael; Elbe‐Bürger, Adelheid
Abstract : Together with keratinocytes (KCs) and the dense network of Langerhans cells (LCs), the epidermis is an ideal portal for vaccine delivery. Pattern recognition receptor agonists, in particular polyinosinic‐polycytidylic acid [p(I:C)], are promising adjuvant candidates for therapeutic vaccination to generate protective T‐cell immunity. Here we established an ex vivo skin explant model to study the expression and activation of double‐stranded RNA (dsRNA)‐sensing pattern recognition receptors in LCs and KCs in human skin. Whereas KCs expressed all known dsRNA sensing receptors at a constitutive and inducible level, LCs exclusively expressed melanoma differentiation‐associated protein 5 (MDA5) in untreated skin and freshly isolated cells. Comparative assessments of downstream signaling pathways induced by p(I:C) revealed distinct mitochondrial antiviral‐signaling protein, IFN‐regulatory factor 3, and NF‐κB activation in LCs and KCs. Consequently, p(I:C) treatment of LCs significantly induced IFN‐α and IFN‐β mRNA expression, while in KCs an up‐regulation of IFN‐β and TNF‐α mRNA was detectable. Stimulation of LCs with specific ligands revealed that not the TLR3‐ but only the MDA5‐specific ligand induced IFN‐α2, IFN‐β, and TNF‐α cytokines, but no IL‐6 and ‐8. In KCs, both ligands induced production of high IL‐6 and IL‐8 levels, and low IFN‐α2 and IFN‐β levels, indicating that different dsRNA‐sensing receptors and/or downstream signaling pathways are activated in both cell types. Our data suggest that MDA5 may be an attractive adjuvant target for epicutaneous delivery of therapeutic vaccines with the goal to target LCs.—Tajpara, P., Schuster, C., Schön E., Kienzl, P., Vierhapper, M., Mildner, M., Elbe‐Bürger A. Epicutaneous administration of the pattern recognition receptor agonist polyinosinic‐polycytidylic acid activates the MDA5/MAVS pathway in Langerhans cells. FASEB J . 32, 4132–4144 (2018). www.fasebj.org